"Antibiotics kill things very quickly" - consumers' perspectives on non-prescribed antibiotic use in Saudi Arabia - Faten Alhomoud; Zainab Aljamea; Lama Basalelah (BMC, 2018)
Abstract Background In recent decades, the Kingdom of Saudi Arabia has seen an exponentially growing antibiotic resistance, which is exacerbated by the use of antibiotics without a prescription and other various factors. However, no published data are available on factors influencing non-prescription use of antibiotics among the general public in Saudi Arabia using an in-depth interview technique. Methods Semi-structured interviews were carried out with 40 Saudi participants from the Eastern Province of Saudi Arabia, selected via snowball sampling technique. Participants were enrolled based on the following inclusion criteria: 18 years of age or older and had self-medicated themselves with antibiotics in the past two years. Data collection was continued until data saturation was attained. Interviews were audiotaped, transcribed verbatim and analysed using NVivo 10 software. Results Participants (80% female) had a mean (SD) age of 30 years (10.2). Self-medication with antibiotics was associated with various inappropriate antibiotic use behaviours and negative outcomes such as antibiotic resistance, treatment failures and adverse events. Interviews revealed that different reasons contribute to the rise of self-medication with antibiotics, ranging from difficulty accessing healthcare services, participant's cultural beliefs and practices, lack of knowledge about antibiotics and antibiotic resistance, and weak regulatory enforcement. Conclusions The findings of the present study will aid in generating data that may provide an insight when designing future interventions to promote public health awareness regarding safe and effective use of antibiotics.